The implementation of PSBB on the development of retail MSMEs with the COVID-19 pandemic as a moderating variable - Trihudiyatmanto, M (Journal of Islamic Economics Management and Business (JIEMB), 2020)
Purpose – This study aims to analyse the effect of the implementation of PSBB on the development of Retail MSMEs (micro, small, and medium enterprises).Method – Respondents in the study were 100 respondents. The sampling technique used in this study was purposive sampling, with the criteria for Retail MSMEs actors in Garung District, Wonosobo Regency, and at least the business had been operating for one year. The data analysis technique used in this research was SEM Smart PLS.Result – The development of Retail MSMEs was significantly influenced by the implementation of PSBB and was moderated by the Covid-19 pandemic. Implication – This study can assist businesses and the government during a pandemic outbreak.Originality – This is the first study examining the influence of a pandemic outbreak on the development of MSMEs in the retail industry.